EKSTERNALITAS TEMPAT PENGOLAHAN SAMPAH TERPADU (TPST) PIYUNGAN KABUPATEN BANTUL DAERAH ISTIMEWA YOGYAKARTA - Widyaningsih, Tri; Ma'ruf, Ahmad (Universitas Muhammadiyah Yogyakarta, 2017)
This research is to analyze both the positive and negative externalities of TPST Piyungan. The objects of this research are the people who lived around TPST Piyungan within the distance of less then 1 km from TPST Piyungan. The primary data are used from questionnaires, observation and interviews with 120 respondents using census method. The analysis in this research is descriptive statistics, income analysis, cost of illness, replacement cost and value added. The results indicate that the existence of TPST Piyungan influenced toward the economical and social aspects as well as the environment of the people around it. The positive externalities value estimation is Rp109.847.940,00/year and the negative externalities value for the people are Rp71.343.000,00/year. Inorganik waste utilization of TPST Piyungan, can give value added Rp632,00/kg for scavengers and Rp392,00/kg for collectors.